Review of the genus Shilovia Makarchenko (Diptera: Chironomidae: Diamesinae: Boreoheptagyiini) from the mountains of Central Asia, with morphological description and DNA barcoding of known species - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2020)
Chironomids of the genus Shilovia Makarchenko (Diamesinae, Boreoheptagyiini) from the mountains of Central Asia are revised using both morphological characters and molecular data. Illustrated descriptions of the adult male Shilovia xinhuawangi sp. nov. from Xinjiang Uygur Autonomous Region of China, S. yakovlevi sp. nov. from East Kazakhstan and redescription of S. rara Makarchenko from Tajikistan and Kyrgyzstan are provided. The result of morphological study is congruent with DNA barcoding analyses using COI sequences. The average K2P interspecific nucleotide distances within S. xinhuawangi sp. nov. and S. yakovlevi sp. nov. are 0.03% and 0.3% respectively. The nucleotide distances between the two new species and S. rara can be considered interspecific. Phylogenetic analysis using Maximum likelihood (ML) and Bayesian inferences (BI) support the placement of S. xinhuawangi sp. nov. and S. yakovlevi sp. nov. within the monophyletic genus Shilovia.